A qualitative exploration of the enablers and challenges that mothers of children with disabilities experience in accessing primary healthcare in Lwandle - Torres, Marcia (2023)
ENGLISH ABSTRACT: Introduction Children with disabilities do need special protection and proper healthcare. The purpose of this study was to gain an insight into the experiences of mothers of children with disabilities on accessing primary healthcare in Lwandle. The main objectives were to identify the enablers and challenges that influenced this healthcare access for their CWD. Methods This study had a qualitative approach to answer the research question. Six mothers of children with disabilities, recruited through total population sampling, participated in the research. In-depth data was gathered by face-to-face interviews which were audio recorded. Data was transcribed and analysed through thematic analysis. Findings Findings of this study highlight six themes which are: Living in the water, Alone and isolated, I am struggling, Spirituality, Helpful healthcare professionals and Family and neighbours. The demands of caring and the mental health challenges that mothers of CWD experience have an impact on accessing PHC for their children. However, spirituality provides mothers with strength and together with caring healthcare professionals and family, these were identified as enablers to PHC access. Conclusion It is critical to also provide the mothers of CWD with optimal care together with their CWD, and the creation of a contextually relevant, multidimensional support system is important going forward to improve health outcomes for CWD.